Pengaruh Pemahaman Materi Fiqih Tentang Shalat Terhadap Praktik Siswa Kelas VII di MTs Muhammadiyah Blimbing Sukoharjo Tahun Ajaran 2025/2026 - Fauzi, Shiddiq Noer; Mujiburrohman, M (Institut Islam Mamba'ul 'Ulum Surakarta, 2026)
This study aims to analyze the effect of understanding the Fiqh material on prayer on the prayer practice of grade VII students at MTs Muhammadiyah Blimbing Sukoharjo in the 2025/2026 academic year. This study uses a quantitative approach with a correlational research type. The subjects of the study were 31 grade VII E students, who were selected using a purposive sampling technique. Data collection techniques were carried out through written tests to measure the level of understanding of the Fiqh material on prayer, observation of prayer practices using a Likert scale to assess student skills, and documentation as supporting data for the study. The data obtained were analyzed using simple linear regression with the help of the SPSS program to determine the relationship and the magnitude of the influence between variables. The results showed that understanding the Fiqh material on prayer had a positive and significant effect on students' prayer practice. This is evidenced by a significance value of 0.000 <0.05 and a t-value of 7.130. Furthermore, the coefficient of determination (R Square) of 0.637 indicates that understanding of Fiqh material contributes 63.7% to students' prayer practice, while the remaining 36.3% is influenced by other factors outside the study. Therefore, the higher the students' understanding of Fiqh material on prayer, the better their prayer practice.